Optimizing in vitro factors for improvement of shoot proliferation of ‘Flordaguard’ peach rootstock - Bianchi, Valmor João (2021)
‘Flordaguard’ has shown great potential as a standard rootstock for peach. The aim of this study was to examine the influence of Murashige & Skoog (MS) medium and modified MS-½N medium (half Nitrogen content), explant type and angle orientation on the culture medium, as well as 6-benzylaminopurine (BAP) concentrations on in vitro shoot proliferation in ‘Flordaguard’ rootstock. Explants cultured in MS-½N medium showed higher averages for number of lateral shoots and elongated shoots. The maximum average length of lateral shoots was obtained using doublephase medium. The 3.0 mg L-1 BAP induced the highest number of lateral shoots per explant (3.38 ±0.57). Whereas the higher number of lateral shoots elongated (1.75 ±0.10 cm) occurred at concentrations until 2.0 mg L-1 BAP. The study corroborated the importance of a 50% reduction in both NH4NO3 and KNO3 content in the cultured medium to improvein vitro propagation of ‘Flordaguard’ peach rootstock.